The evolution of reversed sex roles and classical polyandry: Insights from coucals and other animals. (7th October 2020) - Safari, Ignas; Goymann, Wolfgang
Abstract: In most animals, competition for mating opportunities is higher among males, whereas females are more likely to provide parental care. In few species, though, these "conventional" sex roles are reversed such that females compete more strongly for matings and males provide most or all parental care. This "reversal" in sex roles is often combined with classical polyandry—a mating system in which a female forms a harem with several males. Here, we review the major hypotheses relating such role reversals to evolutionary and behavioural traits (anisogamy, phylogenetic history, sexy males, parental care, genetic paternity, trade‐off between mating and parenting, adult sex ratio) and to ecological factors (food supply, offspring predation). We evaluate each hypothesis in relation to coucals (Centropodinae), a group of nesting cuckoos of great interest for mating system and parental care theory. The black coucal ( Centropus grillii ) is the only known bird combining classical polyandry with altricial development of young, a costly trait with regard to parental care. Our long‐term study offers a unique possibility to compare the strongly polyandrous black coucal with a monogamous close relative breeding in the same area and habitat, the white‐browed coucal ( C. superciliosus ). We show that the evolution of sex roles in coucals and other animals has many different facets. Whereas phylogenetic constraints are important, confidence in genetic paternity is not. In combination with facilitating ecological conditions, adult sex ratios are key to understanding sex roles in coucals, shorebirds, and most likely also other animals. We plead for more studies including experimental tests to understand how biased adult sex ratios emerge and whether they drive sexual selection or vice versa. How do sex ratios and sexual selection interact and feedback on each other? Answers to these questions will be fundamental for understanding the evolution of sex roles in mating and parenting in coucals and other species. Abstract : We reviewed the 8 major hypotheses relating "sex‐role reversal" and classical polyandry to evolutionary, behavioural and ecological factors. First, we evaluate each hypothesis in relation to coucals ( Centropodinae ), a group of nesting cuckoos of great interest for mating system and parental care theory, and then expand the findings to other animal groups and suggest promising avenues of future research.